2020
DOI: 10.1088/1755-1315/601/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Study on influencing factors and influencing strength of urban green space relieving heat island effect—taking Beijing as an example

Abstract: With the acceleration of urbanization, the urban heat island effect has brought a significant impact on the urban environment, and the urban green space can effectively alleviate the heat island effect, but the specific influence intensity is yet to be further studied [1]. In this study, 65 urban green spaces of different sizes and different types within Fifth Ring Road of Beijing were selected through big data analysis to explore the effects of different influence factors such as area, perimeter, shape index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Additionally, various activity sounds intertwined with natural sounds and peripheral traffic sounds to perform various rhythmic soundscapes [32][33][34]. Natural sounds, such as flowing water, wind, vegetation movement and birdsong were positive drivers influencing human perception, while human-generated activity sounds and traffic sounds were negative drivers [35]. We observed correlations between spatial and psychophysical drivers.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, various activity sounds intertwined with natural sounds and peripheral traffic sounds to perform various rhythmic soundscapes [32][33][34]. Natural sounds, such as flowing water, wind, vegetation movement and birdsong were positive drivers influencing human perception, while human-generated activity sounds and traffic sounds were negative drivers [35]. We observed correlations between spatial and psychophysical drivers.…”
Section: Discussionmentioning
confidence: 72%
“…UHIs are affected by various complex natural and human factors. Numerous studies have been conducted to reveal the influencing factors of UHI in different regions through various perspectives, and have noted that the impact factors included the urban underlying surface [46], man-made thermal emissions [47], urban green space scale [48], remote sensing spectral index [49], land use [50][51][52], urban form [53,54], etc. However, the UHI effect might be influenced not only by these conventional factors, but also by more complex factors.…”
Section: Influencing Factors Of Urban Heat Islandsmentioning
confidence: 99%
“…Studies have shown that the types of land used for urban construction and transportation are significantly positively correlated with the urban heat island effect, and cultivated land, forest land, water bodies and other land use types are significantly negatively correlated with the urban heat island effect [ 55 , 94 ]. In the case of the same green area, for every 1% increase in the impervious surface area surrounding a green area, the cooling range of the green area will decrease by approximately 4.01 m [ 95 ]. Lin et al (2007) used the regional atmosphere simulation system MM5 to simulate the urban heat island effect in Beijing; their results showed that water bodies and green spaces have a good control effect on the temperature near the ground [ 96 ].…”
Section: Quantitative Simulations Of the Uste Based On Cfd Considering The Underlying Surface Dynamicsmentioning
confidence: 99%
“…When the proportion of green space reaches 20–35%, the cooling effect will be significantly enhanced, and as the green space proportion increases, the thermal comfort index will increase [ 100 ]. However, the cooling distance range of a green space generally stays between 150 m and 250 m [ 95 ]. Liu et al (2012) simulated the impact of different vegetation types on the urban wind and heat environments based on CFD and found that shrubs hinder the flow field more-so than do trees.…”
Section: Quantitative Simulations Of the Uste Based On Cfd Considering The Underlying Surface Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation